THE ROLE OF BOARDING SCHOOLS IN ESTABLISHMENT AKHLAKUL KARIMAH STUDENTS OF MIFTAHUL MIDAD LUMAJANG ISLAMIC BOARDING SCHOOL - Syulbi, Syulbi (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2023)
This article aims to find out 1. What is the role of Islamic boarding schools in shaping the akhlakul karimah of their students. 2. Management of Islamic boarding schools in shaping the morals of santri. It is known that many educational institutions in Indonesia, especially Islamic boarding schools, have their strategy for forming the akhlakul karimah students. The formation of the akhlakul karimah santri will later impact the alumni produced. Many alumni from Islamic boarding schools have become figures with good morals who have provided many benefits and uswah for the community. So we were moved to write this article to learn more about how Islamic boarding schools form the akhlakul karimah students. This study uses a qualitative method with a case study research type. The data collection techniques used observation and interviews. The data taken is in the form of interview results. The results of this study indicate that the role of Islamic boarding schools in the formation of akhlakul karimah students at the Miftahul Midad Islamic boarding school is to instil values through reciting the book of morals, through the management of the Islamic boarding school, carrying out habituation activities, escorting, exemplary and Islamic boarding school rules. For the sake of forming students who have good morals, Islamic boarding schools do not only provide partial learning. Instead, it provides education for the provision of life as a whole and involves himself with the provision of faith, knowledge, charity, morality, communication/interaction and good intentions. So that students are born who have good morals, always take much initiative, do not wait to be ordered, can create jobs and become uswah for the community. Keywords: the role of Islamic boarding schools, the formation of akhlakul karimah students